Gloss to the decision of the Supreme Administrative Court of 5 April 2016, II FSK 462/14 - Oleksy, Magdalena (Studia Iuridica Toruniensia, 2021)
In the analized ruling, the author critically refers to the decision of the Supreme Administrative Court, in which the court on the one hand states that it is possible to apply the reasoning per analogy in tax cases, and on the other hand, regardless of the analysis, withdraws from this statement, despite indicating the existence of a legal loophole.